Arquitectura, urbanismo y astrología en guadalajara de buga (1998)
From the perspective of a city, this essay enquires whether in HispanicAmerica astral magic was applied in order to structure urban and architectonicspace, as was customary during the reign of Phillip II, suggesting thatastrology was at the heart of the union between architecture, urbanism andart.